Effect of tempering temperature on fatigue strength of Thyssen 6582 steel - Haftirman, Idrus; Ahmad Syayuthi, Abdul Rahman; Mohd Anuar, Mat; Franky, Sutrisno (Universiti Malaysia Perlis, 2009)
Organized by Universiti Malaysia Perlis (UniMAP), 25th - 26th October 2007, Kangar, Perlis.